Implementation of Restorative Justice in Traffic Accident Cases at Sukabumi City Police Station - Haidan Angga Kusumah; Agus Rasyid Chandra Wijaya; Novita Zahra (Yayasan Adra Karima Hubbi, 2023)
Background. The transportation sector is a sector that has an important role in improving the welfare of society. Therefore, the government issued the Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation as a guideline for the creation of safe and comfortable transportation. Purpose. this research aims to find out how the implementation of restorative justice in handling traffic accident cases, especially at Sukabumi City Police. The method used in writing this thesis is a qualitative method with a normative juridical approach. Method. This research uses a normative juridical approach. Normative juridical research is often called theoretical research because normative juridical research discusses doctrines or principles in law. Results. The triggering factors for traffic accidents based on Law No.22/2009 are road negligence and vehicle negligence itself. In addition, there are internal factors that arise from humans such as carelessness, drowsiness, etc. Based on Law No.22 of 2009, there are no other events to resolve traffic accident cases other than criminal justice. However, Police Regulation No. 8 of 2021 on Handling Crimes Based on Restorative Justice provides a way to resolve traffic accident cases with restorative justice. Conclusion. Based on the description above, it can be concluded that the concept of restorative justice is a concept that is expected to complement the shortcomings of the criminal justice system. The implementation of the concept of restorative justice in traffic accident cases in Sukabumi City has been running in accordance with Police Regulation No. 8 of 2021 Handling Crimes Based on Restorative Justice.